Determinants of Anemia in Pregnant Women: A Literature Review on Social, Cultural, and Supplementation Compliance Factors - Zul Ayyun Kurnia Putri; Atika zahria Arisanti (Universitas An Nasher - Cirebon, 2025)
Background: Anemia in pregnant women is a common health problem that can adversely affect both the mother and the fetus. The main causes of anemia during pregnancy include maternal age, education level, occupation, number of previous pregnancies, and the habit of taking iron supplements. Additionally, cultural factors such as myths and dietary restrictions also influence the nutritional intake of pregnant women. Objective: This study aims to explore the factors influencing the incidence of anemia in pregnant women through a review of relevant literature and studies from various sources. Method: A literature review was conducted using credible national and international sources published within the last five years (2019–2024). Articles were selected based on their relevance to anemia during pregnancy and their scientific credibility. Results: The review found that factors such as gestational age, maternal knowledge about anemia, and adherence to iron supplementation significantly affect the incidence of anemia. A lack of education and awareness regarding the importance of taking iron supplements, along with cultural practices that influence dietary habits, can increase the risk of anemia in pregnant women.